Higher Ground: Proposals for a New West Side District Resilient to Wildcat Creek Flooding - Akers, Ashley; Carmichael, Jessie; Chesney, Paden; Cole, Madelyn; Ferrara, Nick; Fitzgerald, Mikala; Hahn, Howard; Herbel, Erich; Jackson, Kastasya; Kappelman, Julia; Madsen, Rainie; Pasowicz, Grant; et al. (Kansas State University. College of Architecture, Planning & Design, Department of Landscape Architecture and Regional & Community Planning., 2019)
This book summarizes the work of the 2019 LAR 646 Community Planning and Design Studio at Kansas State University. The studio explored visioning and design ideas for relocating, restoring, and better protecting businesses and residences affected by the 2018 Wildcat Creek flood event. The areas under consideration are in the southwest and southeast quadrants of the Anderson Avenue and Seth Child Road interchange which is one of the busiest intersections in the city. Periodic flooding renders most of the land south of Anderson vulnerable to future flood damage, forcing many local businesses and residents to abandon their properties. The remaining businesses suffer from the adjacent vacancies, and both Plaza West and Garden Way are facing decline without flood resilience intervention. Large expanses of impermeable surface parking, lack of vegetation, imposing power lines and high traffic volumes make the district unfriendly to pedestrians. The adjoining street corridors also lack visual identity and heavy traffic poses hazards to pedestrians and cyclists. While these conditions challenge existing development, Higher Ground proposes four mixed-use strategies for making the district more resilient: Growing West, KID-hattan, The Compass, and New Corporate Green. The strategies range from maximum preservation of existing natural assets to maximum redevelopment and a new vision for the west side of Manhattan. Concluding the book, a series of “Critical Maps” are presented that informed studio proposals. The studio was supported with funding from the City of Manhattan who provided timely input. Studio activities included site visits, rigorous mapping of various conditions, design development through an iterative process, and a final presentation to the Manhattan Chamber of Commerce and interested stakeholders.
Keywords: Manhattan, KS; Plaza West; Flooding; Flood resilience; Mixed-use development; Wildcat Creek